Serotonin Enhances Megakaryopoiesis and Proplatelet Formation via p-Erk1/2 and F-Actin Reorganization. (14th October 2014) - Ye, Jie Yu; Liang, En Yu; Cheng, Yuan Shan; Chan, Godfrey C. F.; Ding, Yue; Meng, Fanyi; Ng, Margaret H. L.; Chong, Beng H.; Lian, Qizhou; Yang, Mo
Abstract : Our previous studies have shown that serotonin (5-hydroxytryptamine; 5-HT) is a growth factor for hematopoietic stem/progenitor cells. In this study, we proposed a possible mechanism: 5-HT may enhance megakaryopoiesis and proplatelet formation via Erk1/2 pathway and cytoskeleton reorganization. Here, 5-HT2B R was first identified in megakaryocytic cells. 5-HT also promoted the megakaryocytes (MKs) proliferation and reduced the cell apoptosis via the activation of 5-HT2B R and Akt pathway. The effects were reduced by the 5-HT2B R inhibitor ketanserin. The effect of 5-HT on proplatelet formation in bone marrow MKs were further confirmed: the 5-HT treated group had more proplatelet bearing MKs compared with the control group. To determine whether 5-HT has effects on cytoskeleton reorganization of MKs, and whether these effects could be reduced by ketanserin or Erk1/2 inhibitor PD98059, MKs were stained with the F-actin specific binder rhodamine–phalloidin. The polymerized actin level was lower in the control group than the 5-HT group and was distributed throughout the cytoplasm with occasional aggregations. Our data demonstrated that Erk1/2 was activated in MKs treated with 5-HT. This study suggests that 5-HT has a potent effect on platelet formation and this effect is likely mediated via 5HT2B R with subsequent activation of p-Erk1/2 and consequent F-actin reorganization and proplatelet formation. We also demonstrated that melatonin, the metabolite of 5-HT, exerts a protective effect on MK and platelet recovery in the irradiated mouse model. This study suggested that 5-HT plays an important role in platelet formation via 5HT2B R, p-Erk1/2, and F-actin reorganization. Stem Cells   2014;32:2973–2982